Liquid Asset: How Business and Government Can Partner to Solve the Freshwater Crisis - Libecap, Gary D. (Journal of Economic Literature, 2024)
Gary D. Libecap of University of California, Santa Barbara reviews “Liquid Asset: How Business and Government Can Partner to Solve the Freshwater Crisis” by Barton H. Thompson Jr. The Econlit abstract of this book begins: “Examines the growing freshwater challenges facing the United States and the world, focusing on the growing role of private organizations in the US water sector.”